COPING STRATEGIES AMONG INFORMAL SECTOR WORKERS OF MICRO ENTERPRISES: A CASE IN THE CIBURIAL VILLAGE OF KECAMATAN CIMENYAN, BANDUNG DISTRICT - Eri Susanto; Fachry Arsyad (Indonesian Journal of Social Work, 2020)
Coping strategy among informal sector workers of micro-enterprises is motivated by the problem of workers in the informal sector that generally has very low-income levels. In addition, micro-scale informal sector workers also do not have social protection and are vulnerable to work safety such as tire patching, road vendors, roadside stalls, and parking attendants. This study aims to describe the coping strategy undertaken by workers in the informal micro-enterprises sector which includes characteristics, emotional and problems focused coping. The research method used is a qualitative descriptive method with case studies of tire patch workers, food stall waiters, and parking attendants. The informants in this study consisted of 3 (three) main informants and 3 (three) supporting informants. Data collection techniques use interview, observation, and documentation study. The results of the study use qualitative data analysis. Data were tested through the perseverance of observation, the extension of participation, triangulation, and reference material. The results showed that the coping strategy undertaken by informal sector workers of micro-enterprises in handling the problem was not good enough. The emotional focused coping aspect carried out by the informants was more accepting / resigned, thus affecting the problem-focused coping, i.e. there was no planning to find a solution to the problem, less initiative. The action is more about asking for help, borrowing money, that does not solve the problems they are experiencing.